The Impact of Cigarette Consumption and Smoking Duration on the Body Mass Index (BMI) of Students at the Faculty of Agriculture, Methodist University of Indonesia, 2024. - Gabriel Stevani Putri Ndruru; Edwin Anto Pakpahan; Ivonne Situmeang; Endy JuliAnto; Laura Siagian (Jurnal Kedokteran Methodist, 2025)
Background : Smoking is a major global health problem, causing morethan 8 million deaths each year 7 million from direct tobacco use and 1.3million from exposure to secondhand smoke. In Indonesia, the prevalenceof smokers aged 10-18 years increased from 7.2% (2013) to 9.1% (2018),making it the third country with the highest number of smokers. Data fromthe Global Youth Tobacco Survey (2019) shows 40.6% of students aged13-15 years have used tobacco, with 19.2% currently smoking. Body MassIndex (BMI) is used to assess body weight relative to height. Based on the2018 Riskesdas, in Indonesia 9.3% were underweight, 55.3% were normal,13.6% were obese, and 25.8% were obese. Objective: Knowing the impactof the number of cigarettes, the length of smoking and the BMI of studentsof the Faculty of Agriculture, Methodist University of Indonesia Medanbased on the Brikman index in students of the Faculty of Agriculture,University of Indonesia in 2024.Research method: This research is an analytic observational study with aresearch design using a cross-sectional study.Research results: This study found the most students consuming thenumber of cigarettes with < 9 cigarettes / day, as many as 37 respondents(46.3%), then smoking duration found 51 respondents (63.7%) withsmoking duration < 10 years and Body Mass Index found 28 respondents(35%) with body mass index < 18.5. There is a relationship between thenumber of cigarettes with Body Mass Index with a p value = 0.045 (p0.05)and there is a relationship between smoking duration with Body MassIndex with a p value of 0.001 (p0.05). The more influential factor is theamount of cigarette consumption with a p value = 0.013 and OR = 2.4.Conclusion: There is a significant relationship between the number ofcigarettes and body mass index with a p value = 0.045 and there is arelationship between smoking duration and body mass index with a p valueof 0.001.